Structure based discovery of small molecules to regulate the activity of human insulin degrading enzyme. - Bilal Çakir; Onur Dağliyan; Ezgi Dağyildiz; İbrahim Bariş; Ibrahim Halil Kavakli; Seda Kizilel; Metin Türkay (PLoS ONE, 2012)
Background Insulin-degrading enzyme (IDE) is an allosteric Zn(+2) metalloprotease involved in the degradation of many peptides including amyloid-β, and insulin that play key roles in Alzheimer's disease (AD) and type 2 diabetes mellitus (T2DM), respectively. Therefore, the use of therapeutic agents that regulate the activity of IDE would be a viable approach towards generating pharmaceutical treatments for these diseases. Crystal structure of IDE revealed that N-terminal has an exosite which is ∼30 Å away from the catalytic region and serves as a regulation site by orientation of the substrates of IDE to the catalytic site. It is possible to find small molecules that bind to the exosite of IDE and enhance its proteolytic activity towards different substrates. Methodology/principal findings In this study, we applied structure based drug design method combined with experimental methods to discover four novel molecules that enhance the activity of human IDE. The novel compounds, designated as D3, D4, D6, and D10 enhanced IDE mediated proteolysis of substrate V, insulin and amyloid-β, while enhanced degradation profiles were obtained towards substrate V and insulin in the presence of D10 only. Conclusion/significance This paper describes the first examples of a computer-aided discovery of IDE regulators, showing that in vitro and in vivo activation of this important enzyme with small molecules is possible.